Increased serum C-reactive protein concentrations in dogs with congestive heart failure due to myxomatous mitral valve disease. (March 2016) - Reimann, M.J.; Ljungvall, I.; Hillström, A.; Møller, J.E.; Hagman, R.; Falk, T.; Höglund, K.; Häggström, J.; Olsen, L.H.
Highlights: Serum C-reactive protein (CRP) was measured in 184 dogs with different severity of myxomatous mitral valve disease (MMVD). Measurement of serum CRP was performed using a novel canine-specific automated high-sensitivity assay. Serum CRP concentrations were mildly increased in dogs with congestive heart failure due to MMVD. Severity of MMVD in asymptomatic dogs showed no association with serum CRP concentrations. Abstract: Cardiovascular disease in humans and dogs is associated with mildly increased circulating concentrations of C-reactive protein (CRP). Few studies have evaluated associations between circulating CRP and canine myxomatous mitral valve disease (MMVD) and the results reported have been divergent. The aim of this study was to investigate whether serum concentrations of CRP, determined using a novel automated canine-specific high-sensitivity CRP assay (Gentian hsCRP), were associated with severity of MMVD and selected clinical variables in dogs. The study included 188 client-owned dogs with different severities of MMVD. Dogs were classified based on ACVIM consensus statement guidelines (group A, n = 58; group B1, n = 56; group B2, n = 38; group C, n = 36). Data were analysed using descriptive statistics and multiple regression analysis. Dogs with congestive heart failure (CHF; group C) had significantly higher CRP concentrations (median, 2.65 mg/L; quartile 1–quartile 3, 1.09–5.09) compared to dogs in groups A (median, 0.97 mg/L; quartile 1–quartile 3, <0.50–1.97; P = 0.001), B1 (median, 0.78 mg/L; quartile 1–quartile 3, <0.50–1.73, P < 0.0001) and B2 (median, 0.60 mg/L; quartile 1–quartile 3, <0.50–1.23; P < 0.0001). Other variables reflecting disease severity, including left atrial to aortic root ratio ( P = 0.0002, adjusted r 2 = 0.07) and left ventricular end-diastolic diameter normalised for bodyweight ( P = 0.0005, adjusted r 2 = 0.06), were positively associated with CRP concentration, but the association disappeared if dogs with CHF were excluded from analysis. In conclusion, slightly higher CRP concentrations were found in dogs with CHF whereas severity of asymptomatic MMVD showed no association with CRP concentrations.